2016
DOI: 10.1111/raq.12147
|View full text |Cite
|
Sign up to set email alerts
|

Role of deposit‐feeding sea cucumbers in integrated multitrophic aquaculture: progress, problems, potential and future challenges

Abstract: There is significant commercial and research interest in the application of sea cucumbers as nutrient recyclers and processors of particulate waste in polyculture or integrated multitrophic aquaculture (IMTA) systems. The following article reviews examples of existing IMTA systems operating with sea cucumbers, and details the role and effect of several sea cucumber species in experimental and pilot IMTA systems worldwide. Historical observations and quantification of impacts of sea cucumber deposit-feeding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 103 publications
1
66
0
1
Order By: Relevance
“…The integrated farming of vastly different organisms with different needs is complex (Zamora et al, 2016). Challenging is also the optimization of how the extractive species get exposed by the waste-products of the fed species (Troell et al, 2003(Troell et al, , 2009Granada et al, 2016).…”
Section: Position Of Imta Componentsmentioning
confidence: 99%
“…The integrated farming of vastly different organisms with different needs is complex (Zamora et al, 2016). Challenging is also the optimization of how the extractive species get exposed by the waste-products of the fed species (Troell et al, 2003(Troell et al, , 2009Granada et al, 2016).…”
Section: Position Of Imta Componentsmentioning
confidence: 99%
“…Various species of nutrient absorbers, suspension feeders, deposit feeders, and other organic-extractive organisms (Table 1) are candidate organisms that can be co-cultured with the targeted species (finfish, e.g., red sea bream F5, Atlantic salmon F7) in an IMTA system (Zhou et al, 2006;Aveytua-Alcazar et al, 2008;Abreu et al, 2009;Mao et al, 2009;Shi et al, 2011;Yokoyama, 2013;Brito et al, 2014;Yokoyama et al, 2015;Cubillo et al, 2016;Fang et al, 2016;Alexander & Hughes, 2017;Shpigel et al, 2017;Laramore et al, 2018;Zamora et al, 2018). Wastes released from the fish farm can be used as food sources for inorganic and organic nutrient-extractive species.…”
Section: Bio-mitigation Strategy Of Self-pollution: Imtamentioning
confidence: 99%
“…Sea cucumbers are high-value products from marine aquaculture and fisheries; they have also been identified as prospective extractive species for IMTA due to their ability to feed on the particulate waste generated by other animals (Zamora et al 2018). Many studies have shown them to be good candidates for co-culture with finfish (Ahlgren 1998, Hannah et al 2013, Yokoyama 2013, bivalves (Zhou et al 2006, Slater & Carton 2007, Paltzat et al 2008, Yoko yama 2015, gastropods (Kang et al 2003, Maxwell et al 2009) and jellyfish (Ren et al 2014).…”
Section: Introductionmentioning
confidence: 99%